Managerial Performance-Based Education and Training in South Sulawesi - Rusdin Nawi (Khazanah Sosial, 2022)
The purpose of this study to analysis the effect of training service toward performance of managerial, to analysis the effect of training service toward organization governance, and analysis indirect effect the training service through performance of managerial toward organization governance on BPSDM South Sulawesi Province. The research applied on BPSDM South Sulawesi Province with population as amount 583 employees and samples as amount 237 respondent through Slovin formulation. Data from questioner to analysis with path analysis. The result of research with path analysis obtained: the first, implementation of training service have effected toward organization governance in BPSDM. The second, the practice performance of managerial not yet to support the implementation of training service in effect toward organization governance in BPSDM. The result of test showed that the training service have positive and significant toward organization governance. That meaning the implementation of training service, so can to increase the organization governance. better of implementation the training service so the organization governance in BPSDM South Sulawesi Province more increase it.